Hydrograph Separation in the Headwaters of the Shule River Basin: Combining Water Chemistry and Stable Isotopes - Jiaxin Zhou; Jinkui Wu; Shiwei Liu; Guoxiong Zeng; Jia Qin; Xiuna Wang; Qiudong Zhao (Advances in Meteorology)
The runoff components were identified in the headwater area of Shule River Basin, using isotopic and chemical tracing with particular focus on the temporal variations of catchment sources. A total of 95 samples, including precipitation, groundwater, and glacial meltwater, were collected and analyzed for stable water isotopes (18O and 2H) and major chemical ion parameters (potassium, sodium, calcium, magnesium, sulfate, chloride, and bicarbonate). Based on the isotope and water chemistry data, we applied end member mixing analysis (EMMA) to identify and quantify the major runoff generating sources and their contributions. The contributions of groundwater, precipitation, and glacial meltwater were 66.7%, 19.9%, and 13.4%, respectively. The study indicated that groundwater dominated runoff in the headwater area of Shule River Basin. The roles of glacier meltwater should be remarkable in water resource management in this basin. The uncertainties of the EMMA method were summarized and estimated via a classical Gaussian error propagation technique. Analyses suggested that the uncertainty in the measurement method was less important than that in the temporal and spatial variations of tracer concentrations. The uncertainty was sensitive when the difference between mixing components was small. Therefore, the variation of tracers and the difference of mixing components should be considered when hydrograph separation was applied in the basin.